Performance of Combine Harvesters for Sorghum (Sorghum bicolor (L.) Moench) in the Mechanized Rain Fed Schemes of Eastern Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
Direct combine harvesting of crops helps in solving the problem oflabor shortage during harvest period, timely harvest and obtaining good grainquality. A study was conducted in the mechanized rain fed schemes inGedarif State eastern Sudan to evaluate the performance of different combineharvester makes, to quantify harvesting losses and to estimate the value of thelosses for direct harvesting of sorghum. Three combine harvester makes wereassessed, namely; New Holland, Claas and Massey Ferguson. The data wascollected from 46 combine harvesters during three harvesting seasons (2014,2015and 2016). The exact number of each combine harvester make was 21, 9and 16 for New Holland, Claas and Massey Ferguson, respectively. Thecollected data included machine parameters, harvesting losses and economicdata. Results showed that the average forward speed, work rate, fieldefficiency and fuel consumption, was 5.1 km/hr, 2.2 ha/hr, 86% and 7.4 l/ha,respectively. The three harvesters produced similar seed quality in terms ofsound seeds, cracked seeds and impurities. The pre-harvest loss wassignificantly (P ≤ 0.01) the highest among the other loss types. Irrespective toharvester make, the header loss was significantly (P ≤ 0.01) the highestamong machine loss types. No significant differences were noted betweencombine harvester makes in threshing and machine losses. The totalharvesting, machine and collectable losses were 25.1 %, 10% and 19.4 %,respectively. The average value of the pre-harvest loss, machine loss, totalloss and collectable loss was 432.4 SDG/ha, 304.4 SDG/ha, 736.8 SDG/haand 188.9 SDG/ha, respectively. In conclusion, the performance of the threecombine harvesters was technically satisfactory, the machine loss was
Keywords: Harvester work rate and efficiency; harvesting losses; collectable loss; losses value